Use of Artemisinin- Combination Therapies in Port Harcourt - OA Shorinwa; OO Ebong (Journal of Applied Sciences and Environmental Management)
Malaria still constitutes a public health problem in Nigeria and it is the leading cause of morbidity and mortality in Sub –Saharan Africa. The emergence and spread of Plasmodium falciparum parasite resistance to commonly used antimalarials such as chloroquine and  sulphadoxine/pyrimethamine has posed challenges to malaria control. The World Health Organization (WHO) recommends the use of Artemisinin- based combination therapies (ACTs) as the first line of treatment for malaria in Sub –Saharan Africa. This study was carried out to determine the pattern of use of ACTs in Port Harcourt so as to identify problems associated with ACTS use and to contribute to malaria control programme in the country. The parameters investigated include the demography, frequency of malaria attacks, place of treatment, mode of treatment and specific antimalarial drug treatment. A survey was conducted with the aid of structured questionnaires in Port Harcourt metropolis. Of the 717 questionnaires that were returned and evaluated, 690 (96.2%) respondents claimed to have had malaria within the last one year; 244 (34%) received treatment from hospitals; 273 (38.1%) received treatment from pharmacies; 137 (19.1%) engaged in self medication and 17 (2.4%) received herbal treatment. The respondents that took artemisinin based combination drugs were 230 (32.1%), those that took artesunate only were 174 (24.3%), those that took chloroquine were 101 (14.1%) while those that took sulphadoxine/pyrimethamine were 140 (19.5%) while 72 (10%) took other antimalarial drugs. This study suggests that a majority of respondents in the study area take ACTs for the treatment of malaria. @JASEM